Non-Pharmacological Adjuvant Therapies After Botulinum Toxin Injection for Spasticity Control: Narrative Review - Gonçalves, Eduardo Estribio; Serviço de Medicina Física e de Reabilitação, Centro Hospitalar Universitário de Lisboa Central, Lisboa, Portugal (2021)
Introduction: This article aims to expose the current scientific evidence concerning adjuvant therapeutic options of botulinum toxin in the control of spasticity.Methods: A narrative review of the literature published in the Medscape, Cochrane Library and PubMed databases until December 2020 was performed. The terms used in the research were: “botulinum toxin”, “spasticity” and “adjunct therapy”. A total of 137 articles emerged from the research. Case reports, articles of dubious methodological rigor and articles not specifically referring to the objective of the study were excluded. Meta-analysis studies, systematic and narrative reviews as well as controlled and randomized clinical trials were included. After applying the mentioned criteria, 23 articles were selected.Results: The scientific evidence of the different therapeutic options identified was divided into the following categories: physiotherapy/kinesitherapy (stretching, functional training and other interventions), orthoses, plastered immobilizations, functional bands, modified constraint-induced movement therapy and physical agents (electrostimulation, ultrasound, extracorporeal shock waves and vibration). Comparative studies between therapeutic modalities after the application of BoNT-A were also identified.In general, a shortage of evidence for the effectiveness of the various modalities mentioned and, in some cases, evidence of lack of benefit from certain associations was found. Even so, clinical trials with promising interventions were identified, namely the ones that targeted physiotherapy with an association of techniques, electrostimulation, and shock waves therapy. The authors also identified comparative studies that seem to indicate the superiority of electrostimulation and functional bands in relation to stretches, the superiority of shock waves therapy in relation to electrostimulation and the superiority of plastered immobilizations compared to stretches.Conclusion: Prescribing physical therapy with functional training, electrostimulation, shock waves therapy and occasionally using orthoses for intermittent use, may be the most advantageous strategies after the application of BoNT- A. Ultrasound, body vibration and stretching (mainly if applied alone) seem to be less useful. The choice of the specific adjuvant therapy is limited by the available scientific evidence, and the must meet the patient’s, caregivers’ and rehabilitation resources’ particularities.